EXPLORING IN INDONESIAN EFL STUDENTS’ ATTITUDE TOWARDS READING VIA ONLINE SYSTEM - kesuma, henda yani (Al'Adzkiya Journal, 2025)
A good attitude is essential for English reading since it influences how students react toward learning and attitudes in the classroom. The purpose of this study is to determine English students' attitudes on reading via an online system. This study conducted quantitative research. The researcher gathered information via a questionnaire. The researcher analyzed the data using the percentage of the questionnaire and SPSS. This study used primary data from 24 English education department students at the University of Muhammadiyah Sumatera Utara. The conclusions of this study revealed that 18 students (75%) had the most positive attitude, whereas 6 students (25%) had a positive attitude. There were no students connected to the negative. According to the journal that I have read, most students find online learning ineffective and dull. Students have expressed concerns about the impact of the environment and inadequate internet connections on online learning. This research aims to improve the effectiveness of learning media in Indonesia.